1994
DOI: 10.1093/ajcn/59.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone mineral density in children with phenylketonuria

Abstract: Previous studies have suggested that children with phenylketonuria (PKU) have a reduction in bone mineralization compared with control subjects. To investigate this, bone mineral density (BMD) of the total body (TBMD) was measured in 32 prepubertal children with PKU and in 95 age-matched control subjects. Spine bone mineral density (SBMD) was also recorded in a subset, 24 with PKU and 55 control subjects. The effect of dietary intake on bone mass was assessed in 30 of the children with PKU and in 12 control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 13 publications
2
71
1
Order By: Relevance
“…Whether a relatively low calcium supply overcomes the self-regulatory properties of the calciumvitamin D-parathormone system should also be investigated. In fact, adolescent and adult PKU patients have been reported to show decreased bone mineral content (21)(22)(23). Whether calcium is the main contributor to these abnormalities still remains a matter of debate.…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…Whether a relatively low calcium supply overcomes the self-regulatory properties of the calciumvitamin D-parathormone system should also be investigated. In fact, adolescent and adult PKU patients have been reported to show decreased bone mineral content (21)(22)(23). Whether calcium is the main contributor to these abnormalities still remains a matter of debate.…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…However, most previous studies assessing bone quality in PKU (Allen et al 1994;Al-Qadreh et al 1998;Carson et al 1990;McMurry et al 1992;Schwahn et al 1998) did not evaluate bone mineral density (BMD) by the gold-standard method of DXA (Genant et al 1999), reported heterogeneous patient populations (Barat et al 2002;Perez-Duenas et al 2002;Schwahn et al 1998), or comprised only a small number of patients (Barat et al 2002;Schwahn et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Dual-energy X-ray absorptiometry (DEXA) of the spine has shown that phenylketonuric children develop osteopenia [1,4,5]. While the exact reasons for low bone mineral density remain unclear, many explanations have been proposed: the diet being too restrictive [5], poor dietary compliance [2] or a direct effect of the disease [4].…”
mentioning
confidence: 99%